Psychological research of the children with chronic kidney disease and their guardians during the COVID-19 pandemic - Xiong, Hua-Ying; Zhang, Gaofu; Wang, Li; Li, Zhijuan; Shen, Qian; Li, Yuhong; Zhu, Hongtao; Du, Yue; Sun, Liangzhong; Zhao, Bo; Zhao, Lijun; Fu, Haidong; et al. (Frontiers in Public Health, 2022)
Background: There is great mental stress due to the coronavirus disease 2019 (COVID-19) pandemic. However, there are no detailed psychological studies of the children with chronic kidney disease (CKD) and their guardians during the COVID-19 pandemic. Objective: This study explores the psychological pressure on children with CKD and their guardians. Methods: An online survey was conducted at 20 of the largest pediatric nephropathy departments in China, including the Rutter Parent Questionnaire, Self-rating Anxiety Scale (SAS), and Self-rating Depression Scale (SDS). Overall, 885 children (589 children with CKD associated with 296 children of the control group) completed the survey together with their guardians. Results: There was no statistical difference between CKD children and control children regarding their Rutter behavior scores and abnormal behaviors. Nevertheless, the abnormal behavior of children might aggravate the anxiety and depression of guardians in both CKD and control groups (p<0.05). We confirmed that the anxiety and depression of guardians in the CKD group were both significantly higher than those in the control group (p<0.05). The guardians in the CKD group with lower annual income were more likely to experience anxiety (p<0.05). Furthermore, the guardians whose children were older than 11 years old might be more anxious than those who were 6-11 years old. Besides, the guardians in the CKD group who watched the news for 30-60 minutes daily were less likely to have depression than those who watched less than 10 minutes (p<0.05). The subgroup results showed that the gender, the time of watching the news, the annual income of guardians, and children's age might be the most critical factors influencing guardians' psychological burden. Conclusion: The guardians in the CKD group have more severe anxiety and depression during the pandemic. The children's abnormal behavior, adolescents' pressure, low household income, and the panic about the pandemic may be the main reasons for the anxiety and depression of guardians.